Effect of strikes by health workers on mortality between 2010 and 2016 in Kilifi, Kenya: a population-based cohort analysis. Issue 7 (July 2019) - Ong'ayo, Gerald; Ooko, Michael; Wang'ondu, Ruth; Bottomley, Christian; Nyaguara, Amek; Tsofa, Benjamin K; Williams, Thomas N; Bejon, Philip; Scott, J Anthony G; Etyang, Anthony O
Summary: Background: Health workers' strikes are a global occurrence. Kenya has had several strikes by health workers in recent years but their effect on mortality is unknown. We assessed the effect on mortality of six strikes by health workers that occurred from 2010 to 2016 in Kilifi, Kenya. Methods: Using daily mortality data obtained from the Kilifi Health and Demographic Surveillance System, we fitted a negative binomial regression model to estimate the change in mortality during strike periods and in the 2 weeks immediately after strikes. We did subgroup analyses by age, cause of death, and strike week. Findings: Between Jan 1, 2010, and Nov 30, 2016, we recorded 1 829 929 person-years of observation, 6396 deaths, and 128 strike days (median duration of strikes, 18·5 days [range 9–42]). In the primary analysis, no change in all-cause mortality was noted during strike periods (adjusted rate ratio [RR] 0·93, 95% CI 0·81–1·08; p=0·34). Weak evidence was recorded of variation in mortality rates by age group, with an apparent decrease among infants aged 1–11 months (adjusted RR 0·58, 95% CI 0·33–1·03; p=0·064) and an increase among children aged 12–59 months (1·75, 1·11–2·76; p=0·016). No change was noted in mortality rates in post-strike periods and for any category of cause of death. Interpretation: The brief strikes by health workers during the period 2010–16 were not associated with obvious changes in overall mortality in Kilifi. The combined effects of private (and some public) health care during strike periods, a high proportion of out-of-hospital deaths, and a low number of events might have led us to underestimate the effect. Funding: Wellcome Trust and MRC Tropical Epidemiology Group.